Safe Handling of Antineoplastic Drugs During Allergy Diagnostic Workup and Desensitization: A Single Experience of the Allergy Department in a Tertiary Hospital - Berges-Gimeno, María Pilar; Pueyo López, Cristina; Barra-Castro, Alicia; Solano Solares, Emilio; de la Hoz Caballer, Belén (Frontiers in Allergy, 2022)
The increased use of antineoplastic drugs has been associated with a rising number of hypersensitivity reactions to these drugs, which has led to a growth the demand for assistance from allergy services. The involvement of an allergist is essential to ensure these patients with hypersensitivity reactions continue to be able to receive appropriate first-line treatment. Chemotherapy and biological agents have specific handling requirements, and all allergy departments involved in the diagnosis and therapeutic management of patients reacting to these drugs should find the means to guarantee safety. There are currently several guidelines on the safe handling of hazardous drugs for healthcare workers. However, specific recommendations are lacking for reducing occupational exposure in staff working in allergy departments and managing these drugs for the diagnosis and management of hypersensitivity reactions. This review article focuses on the safe handling strategy of the Allergy Department, in the Ramón y Cajal University Hospital and provides details of its implementation and experience over ten years. This protocol could improve the knowledge of safe handling of antineoplastic drugs in allergy procedures.